Village Assistance Through The Development Of Islamic Syiar Programme In Grinting Village Bulakamba Brebes - Purnomo, Halim; Novi, Novi Caroko; Gatot, Gatot Supangkat Samidjo; Widodo, Aris Slamet; Nano, Nano Prawoto; Rahmatika, Dien Noviany (Universitas Pancasakti Tegal, 2022)
Syi'ar Islam must be instilled as early as possible in children through several religious programmes ranging from da'i training, reading and writing the Qur'an and other religious activities. Seeing and referring to today, many children cannot be categorised as individuals with good character and following the teachings of Islam. Without a solid foundation, children will be easily influenced by foreign cultures and habits that are far from good. If from an earl, we began to be formed into from an early age dual with religious ca character, then children can distinguish between good and evil when evil grow up. The Qur'an is a guide to life and will never be eroded by the times. Early childhood equipped with Al-Qur'an education is expected to grow into individuals with noble character. Furthermore, one way to understand the Qur'an is to be able to read and write. In kindergarten, children are provided with Qur'an education by learning to read and write the Qur'an. Educators in kindergarten have carried out assistance, coaching and training of the Qur'an in children with various methods to make it easier to understand and understand and not boring for children.